Desenvolvimento de plataformas nanométricas híbridas baseadas em polímero/enzima visando aplicações em biossensores - Rodrigues, Stanley Endrigo Bilatto (Universidade Federal de São Carlos, 2016)
Foodborne illness cases are common in Brazil and in the world. However, in many cases the microorganism causing the illness cannot properly identified. In addition, traditional analyses usually employed for identifying such microorganisms are often expensive and time consuming. In this context, the development of novel methods capable of detecting such microorganism in a fast way, similarly to a pre-selection method to indicate the positive or negative presence of pathogenic, are highly pursued. In this work, two systems using a concept of Electronic Tongue were developed. The first system used the Layer-by-Layer (LbL) technique to immobilize lysozyme, trypsin and pepsin enzymes in nanostructured films. In the second system, the immobilization process was combined using the LbL technique and covalent bonding for lysozyme and trypsin enzymes. The trypsin and pepsin can react with bacterial sub-products released in the medium, while the lysozyme can react directly with the gram-positive bacteria cell wall. All parameters required to obtain stable films with preserved enzymatic activity were investigated and determined. In the first case, the detection of Escherichia coli using the Electrical Impedance Spectroscopy yielded detection of bacteria at 105 UFC (intermediate values). The second electronic tongue was composed by sensing units formed by lysozyme and trypsin immobilized by covalent and electrostatic (LbL) bonds, allowing the reaction with either by products or with the bacterial cell wall. Contamined solutions with the Gram-positive Staphylococcus aureus, Gram-negative Salmonella bacteria and a mixed solution with both were analyzed. The second system was able to detect small bacteria concentrations at 103 CFU. Finally, the solution re-suspension treatment showed to be beneficial for improving the detection results. The electronic tongue was capable of distinguishing solutions contaminated with bacteria, showing potential to aid in the prevention of foodbourne diseases.
Keywords: Físico-química; Polímeros; Microrganismos; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA